Minimalistic compositional techniques: ‘Glass’ by Hania Rani / Zurfahani Batrisya Zaidi Shamsul, Raja Mohamad Alif Raja Mohamad Adnan and Mohd Yusri Hamid - Zaidi Shamsul, Zurfahani Batrisya; Raja Mohamad Adnan, Raja Mohamad Alif; Hamid, Mohd Yusri (Faculty of Art and Design, 2024)
The purpose of this paper is to investigate the minimalist techniques used in minimalist compositions and to identify the minimalist technique characteristics that cause listeners to perceive the music as minimalist music. This paper also provides information to other composers who require time to learn and familiarise themselves with minimalist techniques. This research seeks to identify the various minimalistic approaches and investigate the melodic progression of "Glass" by Hania Rani, a Polish composer and pianist, and how it has been creatively employed in her composition. The findings from this research will tremendously assist composers and pianists in getting a deeper knowledge of theory and minimalist concepts or procedures. Moreover, the piece 'glass' by Hani Rani is not widely known, and this investigation indirectly introduced the reader to contemporary minimalist composition.